(untitled) (Conference Zone, 2022)
The paper compares the effectiveness of methods of therapeutic gymnastics in water: author’s and generally accepted. The substantiation and content of the developed methodology is presented, which provides for the gradual formation of motor skills that correspond to the process of developing the motor skills of a healthy child. A feature of the technique is the use of physical exercises mainly to suppress tonic muscle reactions and the formation of elements of installation reflexes, as well as the improvement of the psycho-emotional state due to game therapy.